Правова соціалізація дитини як складова процесу розвитку правової свідомості - Опольська, Н.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Статья посвящена исследованию проблем правовой социологии ребенка как составной процесса развития правового сознания. Проанализированы подходы ученых к определению понятия правовой социализации, правовой культуры, правовой сознательности, правового нигилизма. Обоснованы пропозиции дополнения обозначения обозначеных понятий. The article is devoted to research of problems of legal socialization of child as constituent of process of development of legal consciousness. Approaches of research workers are analysed to determination of concept of legal socialization, legal culture, legal consciousness, legal nihilizm. Suggestions in relation to addition of determinations of the noted concepts.